Generalized stem taper and tree volume equations applied to eucalyptus of varying genetics in Brazil - Scolforo, Henrique Ferraco; McTague, John Paul; Burkhart, Harold; Roise, Joseph; Carneiro, Rafaela Lorenzato; Stape, Jose Luiz [UNESP] (Canadian Science Publishing, Nrc Research Press, 2019)
Lack of generalized equations has prevailed in Brazil, because it is assumed that localized or climate-specific equations are needed. This study aimed to develop generalized stem taper and volume equations applicable to 11 eucalyptus clones and evaluate if climate variation impacts the accuracy of the estimates. A total of 693 trees evenly distributed across 11 clones at 21 sites were used for model fittings and predictive validation. The penalized mixed spline (PMS) approach was developed for predicting stem taper and volume along the stem profile. The Schumacher and Hall (1933) equation was used to predict total tree volume, while volume ratio equations were applied to predict merchantable volume. For every fitted equation, an annual climatic variable was included to assess the improvement in model performance. The overall results highlighted that climatic variation does not need to be accounted for in stem taper and volume modeling. All of the equations displayed desirable accuracy, but the generalized PMS equation may be preferred when the forestry enterprise looks to furnish a range of multiple forest products. The generalized total tree volume equation, combined with the ratio equations, is highly recommended when the forestry enterprise produces a single product.
Keywords: penalized mixed spline; volume ratio; climate